Dynamics of host immune response development during Schistosoma mansoni infection - Costain, Alice H.; Phythian-Adams, Alexander T.; Colombo, Stefano A. P.; Marley, Angela K.; Owusu, Christian; Cook, Peter C.; Brown, Sheila L.; Webb, Lauren M.; Lundie, Rachel J.; Borger, Jessica G.; Smits, Hermelijn H.; Berriman, Matthew; et al. (Frontiers in Immunology, 2022)
Schistosomiasis is a disease of global significance, with severity and pathology directly related to how the host responds to infection. The immunological narrative of schistosomiasis has been constructed through decades of study, with researchers often focussing on isolated time points, cell types and tissue sites of interest. However, the field currently lacks a comprehensive and up-to-date understanding of the immune trajectory of schistosomiasis over infection and across multiple tissue sites. We have defined schistosome-elicited immune responses at several distinct stages of the parasite lifecycle, in three tissue sites affected by infection: the liver, spleen, and mesenteric lymph nodes. Additionally, by performing RNA-seq on the livers of schistosome infected mice, we have generated novel transcriptomic insight into the development of schistosome-associated liver pathology and fibrosis across the breadth of infection. Through depletion of CD11c+ cells during peak stages of schistosome-driven inflammation, we have revealed a critical role for CD11c+ cells in the co-ordination and regulation of Th2 inflammation during infection. Our data provide an updated and high-resolution account of how host immune responses evolve over the course of murine schistosomiasis, underscoring the significance of CD11c+ cells in dictating host immunopathology against this important helminth infection.